PARONYMIC RELATIONS IN FIGURATIVE VERBS OF THE KYRGYZ LANGUAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the possibility of the formation of paronymic relations based on the similarity, consonance of the sound form of some figurative verbs in the kyrgyz language. It is noted that there is no special study on paronymy in kyrgyz linguistics. Also, an attempt has been made to classify the paronymic series of figurative verbs based on the consonant model.
Keywords: kyrgyz language, figurative verbs, sound form, affinity, consonance, difference, paronymy, paronymic series, consonant model, artistic style